Comprehending and improving cannabis specialized metabolism in the systems biology era. (September 2020) - Romero, P.; Peris, A.; Vergara, K.; Matus, J.T.
Abstract: Cannabis sativa is a source of food, fiber and specialized metabolites such as cannabinoids, with psychoactive and pharmacological effects. Due to its expanding and increasingly-accepted use in medicine, cannabis cultivation is acquiring more importance and less social stigma. Humans initiated different domestication episodes whose later spread gave rise to a plethora of landrace cultivars. At present, breeders cross germplasms from different gene pools depending on their specific use. The fiber (hemp) and drug (marijuana) types of C. sativa differ in their cannabinoid chemical composition phenotype (chemotype) and also in the accumulation of terpenoid compounds that constitute a strain's particular flavor and scent. Cannabinoids are isoprenylated polyketides among which cannabidiolic acid (CBDA) and (−)-trans-Δ⁹-tetrahydrocannabinol acid (THCA) have been well-documented for their many effects on humans. Here, we review the most studied specialized metabolic pathways in C. sativa, showing how terpenes and cannabinoids share both part of the isoprenoid pathway and the same biosynthetic compartmentalization (i.e. glandular trichomes of leaves and flowers). We enlist the several studies that have deciphered these pathways in this species including physical and genetic maps, QTL analyses and localization and enzymatic studies of cannabinoid and terpene synthases. In addition, new comparative modeling of cannabinoid synthases and phylogenetic trees are presented. We describe the genome sequencing initiatives of several accessions with the concomitant generation of next-generation genome maps and transcriptomic data. Very recently, proteomic characterizations and systems biology approaches such as those applying network theory or the integration of multi-omics data have increased the knowledge on gene function, enzyme diversity and metabolite content in C. sativa . In this revision we drift through the history, present and future of cannabis research and on how second- and third-generation sequencing technologies are bringing light to the field of cannabis specialized metabolism. We also discuss different biotechnological approaches for producing cannabinoids in engineered microorganisms.